2015
DOI: 10.4194/1303-2712-v15_2_12
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: The effects of feeding-intensity stress on biochemical indices of the GIFT strain of Nile tilapia were investigated in a recirculating freshwater system. Differences in serum and liver biochemistry, routine blood measurements, and growth were examined in fish fed three experimental rations (2%, 4% and 6% of fish biomass daily). Larger rations led to higher SGR but lower FCR, PER and SR. Smaller rations caused higher levels of HSI and cortisol. Fish on the 2% and 6% diets had lower liver levels of C3, LZM, SOD,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 44 publications
1
5
0
Order By: Relevance
“…Our result was coming agree with that of Hel et al (38) in term of the relatively high LDH activity in liver tissues of the infected fish. She recorded an increase in blood glucose and LDH activity in tissues of Tilapia fish those infected with metacercariae of the Pyigidiopsis summa and Geneta cestodes.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Our result was coming agree with that of Hel et al (38) in term of the relatively high LDH activity in liver tissues of the infected fish. She recorded an increase in blood glucose and LDH activity in tissues of Tilapia fish those infected with metacercariae of the Pyigidiopsis summa and Geneta cestodes.…”
Section: Discussionsupporting
confidence: 94%
“…She recorded an increase in blood glucose and LDH activity in tissues of Tilapia fish those infected with metacercariae of the Pyigidiopsis summa and Geneta cestodes. Hel et al (38) correlated between the increment in LDH activity in the infected fish with the elevation in anaerobic catabolism of blood glucose as a result of liver and muscle tissues damage.…”
Section: Discussionmentioning
confidence: 99%
“…Biochemical biomarkers such as total proteins, total lipids, cholesterol, are powerful biomarkers which are usually utilized under stress conditions in assessing the general health status of fish. Due to the closed relation between the circulatory system of fish and the external environment, fish physiology including biochemical parameters and metabolic enzymes are favorable tools in monitoring water quality in aquatic environments ( He et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…Haematological indices play a critical role in the assessment of health and diagnosis of diseases in fish (He et al, 2015) TA B L E 1 Characteristics of blood physiological of wild, factory-cultured and cage-cultured Hexagrammos otakii the management of cultured fish (De Moraes et al, 2017). Our results demonstrated that haemoglobin (Hb) levels were significantly higher in the WF group than that in the cultured groups, which might be due to the relatively fast combination rate of CO and O 2 with Hb, providing a comparatively high resistance to oxygen and a lower haematocrit (HCT) in fish subjected to hyperoxic conditions (Holland & Fokster, 1966;Ruyet et al, 2002).…”
Section: Discussionmentioning
confidence: 99%